Treatment indications for and outcome of endovascular repair of type B intramural aortic hematoma - Bischoff, Moritz; Meisenbacher, Katrin; Wehrmeister, Michael; Böckler, Dittmar; Kotelis, Drosos (Journal of vascular surgery, 2016)
Objective - The aim of this study was to analyze the outcome of thoracic endovascular aortic repair (TEVAR) and medical therapy in patients with aortic intramural hematoma type B (IMHB). - Methods - Between January 2004 and January 2014, 41 IMHB patients were treated; 28 underwent TEVAR (16 male; median age, 69 years; group I) plus best medical therapy (BMT), whereas 13 had BMT alone (6 male; median age, 69 years; group II). Study end points were assessment of indications for TEVAR and BMT, clinical outcome, and evaluation of aortic morphology over time. Median follow-up was 32 months for group I and 40 months for group II. - Results - In group I, TEVAR was immediately performed in 7 of 28 cases because of pain and imaging results (penetrating aortic ulcers, n = 4; intramural blood pools, n = 3). In 21 of 28 cases, TEVAR was undertaken because of clinical or radiologic signs of progression at a median of 10 days (range, 2-223 days). The median number of stent grafts implanted was two (range, 1-3). The median length of covered aorta was 15 cm (range, 9.5-33.4 cm). Technical success was achieved in 25 of 28. In-hospital mortality was 1 of 28 in group I and 0 of 13 in group II. Survival in group I was 81.5%, 77.8%, and 67% at 1, 2, and 4 years. There was no death in group II during follow-up. Aortic reinterventions were performed in 6 of 28 group I cases, including 2 open conversions for retrograde type A dissection. Aortic diameter decreased during follow-up in 10% in group I (vs 3% in group II; P = .039). In group I, complete remodeling was seen in 7 of 27, regression in the remaining 20. In group II, complete remodeling was seen in 3 of 12; regression was seen in 9 of 12. No patient in group II required invasive treatment. - Conclusions - BMT is justified in uncomplicated IMHB. However, IMHB becomes complicated in the majority of patients within 20 days. TEVAR in complicated IMHB is feasible but associated with a substantial aortic reintervention rate, reflecting technical challenges and fragile aortic wall conditions.